Perioperative hair removal in the twenty-first century: utilizing an innovative vacuum-assisted technology to safely expedite hair removal prior to surgery - Edmiston, Charles E.; Griggs, Russell K.; Tanner, Judith; Spencer, Maureen; Seabrook, Gary R.; Leaper, David (Elsevier, 2016)
Background